The Effect Of Agricultural Sector Labor, Agricultural Sector Exports, And Agricultural Sector Investment On Economic Growth With Technology As A Moderating Variable - Ariefqi, Muhamad Yufa; Diyah Ariyani (Journal of Economics and Business Aseanomics, 2025)
The role of the agricultural sector on economic growth is the main focus of this study. This study aims to analyze the effect of labor, exports, and investment in the agricultural sector on economic growth in Indonesia with technology as a moderating variable. This type of research is quantitative using time series data covering the period 2012-2023. The analysis method used is Panel Data Regression Analysis and Moderation Regression Analysis (MRA) using the STATA application. The results showed that agricultural sector labor had a positive and significant effect, and technology was unable to moderate its relationship to economic growth. While agricultural sector exports have a negative and insignificant effect, and technology is able to moderate its relationship to economic growth, agricultural sector investment has a significant negative effect and technology is able to moderate its relationship to economic growth. In the F test, it was found that the independent variables together had a significant effect on economic growth